Comparative effectiveness of silvicultural interventions for increasing timber production and sustaining conservation values in natural tropical production forests: A systematic review protocol - Petrokofsky, G.; Sist, P.; Blanc, Lilian; Doucet, J.L.; Finegan, B.; Gourlet-Fleury, S.; Healey, J.R.; Livoreil, B.; Nasi, Robert; Peña-Claros, M.; Putz, F.E.; Zhou, W. (Springer, 2015)
Currently, about 400 million hectares of tropical moist forests worldwide are designated production forests, about a quarter of which are managed by rural communities and indigenous peoples. There has been a gradual impoverishment of forest resources inside selectively logged forests in which the volume of timber extracted over the first cutting cycle was mostly from large, old trees that matured over a century or more and grew in the absence of strong anthropological pressures. In forests now being logged for a second and third time, that volume has not been reconstituted due in part to the lack of implementation of post-logging silvicultural treatments. This depletion of timber stocks renders the degraded forests prone to conversion to other land uses. Although it is essential to preserve undisturbed primary forests through the creation of protected areas, these areas alone will not be able to ensure the conservation of all species on a pan-tropical scale, for social, economic and political reasons. The conservation of tropical forests of tomorrow will mostly take place within human-modified (logged, domesticated) forests. In this context, silvicultural interventions are considered by many tropical foresters and forest ecologists as tools capable of effectively conserving tropical forest biodiversity and ecosystem services while stimulating forest production. This systematic review aims to assess past and current evidence of the impact of silviculture on tropical forests and to identify silvicultural practices appropriate for the current conditions in the forests and forestry sectors of the Congo Basin, Amazonia and Southeast Asia. This systematic review will undertake an extensive search of literature to assess the relative effectiveness of different silvicultural interventions on timber production and the conservation value of forests, and to determine whether there is a relationship between sustainability of timber harvesting and the maintenance/conservation of other ecosystem services and biodiversity in production forests. Data will be extracted for meta-analysis of at least sub-sets of the review questions. Findings are expected to help inform policy and develop evidence-based practice guidelines on silvicultural practices in tropical forests.